2014
DOI: 10.1039/c4tc01010h
|View full text |Cite
|
Sign up to set email alerts
|

Water dispersible electrically conductive poly(3,4-ethylenedioxythiophene) nanospindles by liquid crystalline template assisted polymerization

Abstract: Formation of nanospindles of PEDOT through liquid crystalline template polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…The band maxima measured at 978 cm −1 in EDOT of C−S were observed to be shifted to 889 cm −1 in EDOT-PDPPA. 21 These observed shifts in the characteristic bands of EDOT and PDPPA in the FTIR spectrum of EDOT-PDPPA reveal the presence of various types of molecular interactions between these two molecules during the formation of the adduct. EDOT-PDPPA can form self-assembled supramolecular architectures through various interactions such as Coulombic forces among hydrophilic cations (phosphonium δ+ ) and anions (thiophene δ− ) present in the ionic head groups and also form interdigitated self-assembled structure via antiparallel stacking of the hydrophobic alkyl chains through electrostatic layer by layer assembling.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 94%
See 1 more Smart Citation
“…The band maxima measured at 978 cm −1 in EDOT of C−S were observed to be shifted to 889 cm −1 in EDOT-PDPPA. 21 These observed shifts in the characteristic bands of EDOT and PDPPA in the FTIR spectrum of EDOT-PDPPA reveal the presence of various types of molecular interactions between these two molecules during the formation of the adduct. EDOT-PDPPA can form self-assembled supramolecular architectures through various interactions such as Coulombic forces among hydrophilic cations (phosphonium δ+ ) and anions (thiophene δ− ) present in the ionic head groups and also form interdigitated self-assembled structure via antiparallel stacking of the hydrophobic alkyl chains through electrostatic layer by layer assembling.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 94%
“…20 We have recently reported the preparation of water dispersible PEDOT nanospindles through chemical polymerization from the liquid crystalline phase of the spindle shaped smectic phase. 21 We have observed that the ordered molecular chains in the polymer imitated the anisotropic nature of the monomer. The shape and ordering of the liquid crystalline monomer are locked in PEDOT in the nanometer regime due to the thermodynamic influence of the growing chain.…”
Section: ■ Introductionmentioning
confidence: 97%
“…[1][2][3] Albeit lithium batteries have a major dependence on the performance of electrodes, it is often demonstrated that electrolytes do limit the voltage window, charge transport, and conductivity and thereby the corresponding energy density, power density, and cycle life of the energy storage systems. [32][33][34] Also, we have recently studied the synthesis and liquid crystalline properties of ammonium and imidazolium-based ionic liquid crystalline materials derived from cardanol. But the leakage of volatile and toxic liquid electrolytes upon crimping the cell or during full paper domains and channels of 1D, 2D, and 3D ordered type are expected to facilitate the shuttling of Li + ions during charge and discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported several derivatives of this molecule, which were applied for the preparation of coatings, adhesives, liquid crystalline templates, and as dopants for the preparation of nanostructured conducting polymers. [32][33][34] Also, we have recently studied the synthesis and liquid crystalline properties of ammonium and imidazolium-based ionic liquid crystalline materials derived from cardanol. [35,36] These films are expected to exhibit better electrolyte affinity in comparison with the commonly explored polyolefinic separator membranes, owing to the presence of amphiphilic hydrocarbon chain.…”
Section: Introductionmentioning
confidence: 99%
“…PPy hollow nanoparticles with different diameters were prepared by surfactant templating and their electrical properties depended on the size. Devaki et al [68,69] explored liquid crystalline templates with an inexpensive and abundantly available industrial by-product, the main constituent of cashew nut shell extract, namely, cardanol (3-pentadecylphenol). This approach might be a good alternative to traditional petroleum-based surfactants, which have become expensive owing to increased demand and depletion of resources.…”
Section: Recent Advances In the Synthesis Of Cp Nanomaterialsmentioning
confidence: 99%